Reactive Oxygen Species (ROS) in Living Cells 2018
DOI: 10.5772/intechopen.72217
|View full text |Cite
|
Sign up to set email alerts
|

Role of Antioxidant Phytochemicals in Prevention, Formation and Treatment of Cancer

Abstract: Reactive oxygen species (ROS) played an important role in cancer. Although low levels of ROS can be beneficial in normal physiological functions, chronic exposure to ROS is associated with increased risk of cancers. Increased ROS levels can also induce apoptosis and cell death in various types of cancer. Taken together, the role of ROS in cancer prevention, formation and therapy is extremely complex and very challenging to study. Although the antioxidant activity of phytochemicals is well recognized and genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 171 publications
(213 reference statements)
4
17
0
Order By: Relevance
“…The results herein obtained in GA-treated cells at concentrations sub-active of GA confirm those obtained in the time-course and dose-dependent experiments, which show that, as reported previously [23,24], GA cytotoxic action is dose dependent and is performed only at high dosage, similar to many natural antioxidant-pro-oxidant compounds [97].…”
Section: Evaluation Of Cytotoxic Action Of Gad Gald Ga and Empty Desupporting
confidence: 90%
See 2 more Smart Citations
“…The results herein obtained in GA-treated cells at concentrations sub-active of GA confirm those obtained in the time-course and dose-dependent experiments, which show that, as reported previously [23,24], GA cytotoxic action is dose dependent and is performed only at high dosage, similar to many natural antioxidant-pro-oxidant compounds [97].…”
Section: Evaluation Of Cytotoxic Action Of Gad Gald Ga and Empty Desupporting
confidence: 90%
“…In addition, as reported for many other kinds of tumors [98], these findings confirmed that, also on NB cells, GA exerts a ROS-mediated cytotoxic anticancer activity at high doses, while it loses its pro-oxidant properties at low doses [97].…”
Section: Time-course and Dose-dependent Experiments On Gasupporting
confidence: 83%
See 1 more Smart Citation
“…However, natural chemotherapy drugs from herbal plants, which may induce apoptosis in cancer cells, can serve as chemotherapeutic agents [3]. Besides that, natural compounds that have high antioxidants have been demonstrated to have a protective effect against cancer development [4].…”
Section: Introductionmentioning
confidence: 99%
“…As dietary phytochemicals lack mechanistic selectivity, these natural compounds display a variety of effects in different cancer cell types and thus the discrepancies in results among separate studies. Other possible reasons for divergent findings in different studies include changes or differences in (i) stability of the bioactive compounds in cell culture medium, for example, stability of Qu decreases at pH 7 or 8 [175]; (ii) release of bioactive compounds under different conditions, for example, the maximum release of curcumin occurs in phosphate buffered saline at pH 6.4 [176]; (iii) sensitivity of different cell types to bioactive compounds; (iv) cellular permeability of bioactive compounds; (v) presence or contamination by metal ions [177]; (vi) number of hydroxyl groups present in a molecule [177]; and (vii) in vivo biodistribution.…”
Section: Limitationsmentioning
confidence: 99%